The Shift Paradigm of the Death Penalty in the Draft Criminal Code - titin nurfatlah; Amiruddin Amiruddin; Ufran Ufran (Unram Law Review, 2020)
This study aims to determine the concept of the death penalty in the future Indonesian criminal law. The method used is a normative research method. The approaches in this research are the statute approach, conceptual approach, historical approach, and comparative approach. The conclusion based on the results of the research, the death penalty in the Draft of the Penal Code is no longer a primary punishment but has separate rules. The provisions of the death penalty in the Draft Penal Code is particular and as an alternative punishment. The purpose of this death penalty provision includes giving broader consideration for judges in giving decisions as not arbitrary towards the convicted; give more attention to the objectives of the punishment. Additionally, the provision advocates the death penalty as a last resort in protecting the community, as the judges shall look for other punishment as an alternative to the death penalty. The Draft of the Criminal Code bases on Neo-Classical school of thought, which maintains a balance between objective factors (actions/outward) and subjective factors (people/ inner/inner attitudes).